Safety evaluation study of lincomycin and spectinomycin hydrochloride intramuscular injection in chickens - Ejaz Ali Khan; Jifei Ma; Meng Xiaobin; Yang Jie; Liu Mengyue; Liang Hong; Luqman Shah; Ailing Liu (Toxicology Reports, 2022)
This study aimed to investigate the nonclinical safety of lincomycin and spectinomycin hydrochloride (LC-SPH) intramuscular (i.m) doses on target animals (chickens) to provide guidelines for dose level design and side effect monitoring in clinical trials.A total of 80 healthy Arbor Acres plus broiler chicks were completely randomized and blindly divided into four treatment groups (control, one-time dose, three-time dose, and five-time dose) of 20 chicks each (20 chickens per group). At the age of day 15, all chickens (except the control group) were administered LC-SPH intramuscularly (chest muscles) at different doses of 20 mg/kg.bw, 60 mg/kg.bw, and 100 mg/kg.bw respectively for 9 consecutive days recommended by veterinary international cooperation on harmonization (VICH) guidelines. The chickens had ad libitum access to antibiotic-free feed and water. Feeding chickens were observed twice a day throughout the study. The drug safety was evaluated by complete blood count, biochemical parameters, histopathological, clinical signs, body weight gain, and feed conversion ratio (FCR).Hence, considering the minor toxicity of 60 mg/kg, our results reveal that intramuscular injection of at least 20 mg/kg body weight has no effects on growth performance, clinical blood parameters, organ coefficient, and histopathological parameters. Thus, a combination of LC-SPH 20 mg/kg body weight i.m injection investigated safe followed daily administration for nine consecutive days in healthy chickens.It is concluded that the experimental results support the safety of 20 mg/kg body weight in combination for the further clinical research study.